Japan : Financial Sector Assessment Program-Technical Note-Insurance Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Japan in the areas of insurance sector regulation and supervision. The Japanese insurance sector is characterized by a mature market, high concentration, and the predominance of life insurance products with interest guarantees. It is recommended that the Japan Financial Services Agency (JFSA) should take further steps to implement an economic-value-based solvency regime as soon as practicable. A risk assessment methodology needs to be completed as part of the risk-based supervision framework. The risk and impact assessment will enable JFSA to determine the appropriate supervisory intensity for each insurer, and a holistic supervisory plan.